Aortocaval fistula, a potentially favourable complication of abdominal aortic aneurysm rupture in endovascular repair - Greenfield, S (Ann R Coll Surg Engl, 2020)
Endovascular aneurysm repair is an established treatment for ruptured abdominal aortic aneurysm. Primary aortocaval fistula is an exceedingly rare finding in ruptured abdominal aortic aneurysm, with a reported incidence of less than 1%. The presence of an aortocaval fistula used to be an unexpected finding in open surgical repair which often resulted in massive haemorrhage and caval injury. We present a case of ruptured abdominal aortic aneurysm with an aortocaval fistula that was successfully treated with percutaneous endovascular aneurysm repair under local anaesthesia. Despite a persistent type 2 endoleak the aneurysm sack shrank from 8.4cm to 4.8cm in 12 months. The presence of an aortocaval fistula may have depressurised the aneurysm, resulting in less bleeding retroperitoneally and may have promoted rapid shrinkage of the sac despite the presence of a persistent type 2 endoleak.